The outer wind of gamma Velorum - Roche, P; Colling, MD; Barlow, M (2012)
Fine-structure mid-infrared emission lines with critical densities in the regime 10 4 ≤ n crit ≤ 10 6cm -3 can be employed to probe the outflow from Wolf-Rayet (WR) stars at radii of ~10 15cm. Narrow-band mid-infrared imaging and spectroscopy of the nearest WR star to the Sun, γVelorum is analysed for spatially resolved forbidden line emission in the WR outer wind. The [Siv] 10.52-μm and [Neii] 12.81-μm emission regions are found to be spatially extended, compared to unresolved continuum and He and C recombination line emission. The [Siv] and [Neii] emission line distributions have a high degree of azimuthal symmetry, indicating a spherically symmetric outflow. A model wind with a modest degree of clumping (clumping factor f ~ 10) provides a better match to the observations than an unclumped model. The overall line intensity distributions are consistent with a freely expanding, spherically symmetric 1/r 2 outflow with constant ionization fraction and modestly clumped density structure. © 2012 The Authors Monthly Notices of the Royal Astronomical Society. © 2012 RAS.